Development of a PLA/PHA-TiO2 Polymer Blend with Improved Physicochemical and Thermal Properties - Qader, Ibrahim Nazem; Kok, Mediha; Mohammed, Kathrin Sleman; Coskun, Meltem; Oner, Ecem ozen; Aydogdu, Yildirim (Springer, 2025)
The increasing use of plastic products has led to significant environmental concerns from waste accumulation and inadequate recycling, highlighting the need for sustainable solutions like biodegradable plastics. This study investigates the influence of titanium dioxide nanoparticles (TiO2 NPs) on the structural, thermal, and mechanical properties of polylactic acid (PLA) and polyhydroxyalkanoate (PHA) polymer blends, focusing on their shape memory behavior and crystallinity. The PLA/PHA: TiO2 nanocomposites, synthesized via solution casting, were characterized by XRD, DSC, TGA, SEM, SME, FTIR, and tensile testing. XRD analysis confirmed the incorporation of highly crystalline tetragonal TiO2 NPs (space group I41/amd), which increased the overall crystallinity of the composites while reducing the crystallinity of the PLA/PHA blend. Thermal analysis revealed a decrease in the blend's glass transition temperature (T-g) from 36.5 degrees C to lower values with TiO2 doping, while the melting temperature (T-m) remained stable at approximately 175.3 degrees C. SEM micrographs demonstrated uniform nanoparticle dispersion, with surface roughness increasing at higher TiO2 concentrations. Tensile testing showed a reduction in elasticity and a progressive increase in stiffness with increasing TiO2 content, while UV-Vis analysis revealed a decrease in the bandgap energy to below 4 eV due to enhanced charge carrier density. This study pioneers the use of TiO2 NPs to enhance the crystallinity, thermal stability, and shape memory properties of PLA/PHA blends, offering a promising pathway for advanced environmentally friendly material applications.
Keywords: TiO2 NPs; PLA/PHA blend; Nanocomposites; Tensile test; Shape memory recovery